2011
DOI: 10.1016/j.bpj.2011.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Hydration Properties of Wild-Type and Familial Point Mutant A53T of α-Synuclein Associated with Parkinson's Disease

Abstract: The propensity of α-synuclein to form amyloid plays an important role in Parkinson's disease. Three familial mutations, A30P, E46K, and A53T, correlate with Parkinson's disease. Therefore, unraveling the structural effects of these mutations has basic implications in understanding the molecular basis of the disease. Here, we address this issue through comparing details of the hydration of wild-type α-synuclein and its A53T mutant by a combination of wide-line NMR, differential scanning calorimetry, and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 42 publications
4
64
0
Order By: Relevance
“…We could provide evidence that the protein Df31 (Drosophila melanogaster histone chaperone involved in chromatin decondensation and stabilization) is intrinsically disordered along its entire length [20], the entire proline-rich region of CASK-interactive protein1 is intrinsically disordered [21], and that the results depend also on the protein structure (primary to quaternary level) [22] and its propensity to form a complex [23]. It was also found that a living organ, the eye lens, which contains various kinds of crystallins [24] in high concentrations, has characteristics similar to the protein solutions concerning the "non-freezing water phase" [25].…”
Section: Water Molecules Map the Interfacial Spacementioning
confidence: 99%
See 2 more Smart Citations
“…We could provide evidence that the protein Df31 (Drosophila melanogaster histone chaperone involved in chromatin decondensation and stabilization) is intrinsically disordered along its entire length [20], the entire proline-rich region of CASK-interactive protein1 is intrinsically disordered [21], and that the results depend also on the protein structure (primary to quaternary level) [22] and its propensity to form a complex [23]. It was also found that a living organ, the eye lens, which contains various kinds of crystallins [24] in high concentrations, has characteristics similar to the protein solutions concerning the "non-freezing water phase" [25].…”
Section: Water Molecules Map the Interfacial Spacementioning
confidence: 99%
“…The differences between the MDs of E46K-and WT-aS demonstrate, that wide-line NMR is able to make clear distinction between point mutants (for the experimental details see [22]; detailed interpretation will be published separately).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Destabilization of the native state is promoted by disease-associated mutations, as was shown in MD studies for A53T (Coskuner and Wise-Scira, 2013), A30P (Wise-Scira et al, 2013a), and E46K (Wise-Scira et al, 2013b). Structural changes promoted by these mutations result in more open states, biased to aggregation (Hazy et al, 2011). Results of atomistic simulations (Tsigelny et al, 2008) suggest that the transient oligomers formed by a-synuclein may be the species capable of interacting with lipid membranes.…”
Section: Sod1 and Alsmentioning
confidence: 74%
“…Differences in the structural and hydration properties of amyloid fibrils formed by wild type (WT) aSN and the two PD-linked mutants, A30P and A53T, have been reported [12,13]. More recently, it has been revealed by solid state NMR that fibrils obtained from A53T aSN in vitro show some structural variations in the core with respect to fibrils of the WT protein [14,15], while the same effect was not observed for A30P aSN fibrils [16].…”
Section: Introductionmentioning
confidence: 99%